Anti-diabetic formulation obtained from Albizzia myriophylla extract. - Rosli, Rozita (2011)
In this regard the present invention intends in a first aspect to solve the problem of providing novel formulation for treating the above mentioned disease by obtaining gajah Albizzia myriophylla bark extract. More particularly, the present invention is a formulation obtained from Albizzia myriophylla bark extract and/or combining coconut oil in the preparation of a medicament for treating and/or preventing diabetes mellitus.